Performance of organic dyes for textile cotton fabric - Singam, Rupashinii Thana; Marsi, Noraini; Hamzah, Azrul Azlan; Mohd Yasin, Faisal (UNIMAP, 2020)
This research was focus on optimum dye concentration for self-cleaning properties for uncoated and coated dyed cotton fabrics through physical and mechanical properties. The dyed cotton fabrics were coated with aqueous emulsion C6-fluorocarbon. C6-fluorocarbon is an organic coating consisting of solid particles where it will dissolve in a specific formulated solvent. Cotton fabrics have cellulose and abundant hydroxyl groups structure where it will make hydrophilic properties where the fiber can provide an appropriate environment for microorganism growth in contact with water and sweats. Therefore, aqueous emulsion C6-fluorocarbon was coated as a hydrophobic coating to overcome the problem of dyed cotton fabric. Moreover, this research was aim to find the optimum concentration of dye with superhydrophobic layer and the comparison of natural dyes with synthetic dye, Golden Yellow with physical and mechanical tests. The test involved were water contact angle, crocking, weather resistance of fabric, washing, abrasion and bursting test. It was found that F (wt/wt%) was the optimum dye concentration and has the highest contact angle. The coated dyed fabric has higher mechanical and physical properties compared to the uncoated dyed fabric which can replace the usage of synthetic dye.